NARRATIVE OF MAGIC REALISM IN THE JOHN BELLAIRS’ NOVEL: THE HOUSE WITH THE CLOCK IN ITS WALLS - Vany Rizkita Laily (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2020)
This research aims to analyze the relationship between the novel written by John Bellairs entitled The House With A Clock In Its Walls and the magical elements of realism. By using Wendy B. Faris magic realism theory which focuses on the five characters of magic realism, namely, irreducible, phenomenal world, unsettling doubt, merging of nature, and the disturbance of time, space and identity. This research also uses a descriptive qualitative approach. Through this approach, this research can find the results that the five elements or characters of magical realism can be found in the novel.